ENVELOPE SOLAR: FERRAMENTA DE ANÁLISE DA LEGISLAÇÃO URBANÍSTICA PARA GARANTIA DO ACESSO SOLAR - ESTUDO NO PLANO DIRETOR DO MUNICÍPIO DE SÃO LOURENÇO DO SUL-RS - Schneid, Andréia; Correa, Celina Maria Britto (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
This study presents an application of the Envelope Solar (ES) method directed to urban planning, as a way of demonstrating its support for the formulation of urban regulations, specifically in the Sustainable Development Master Plan (PDDIS) of the São Lourenço do Sul, 2006, which began to be revised in 2018. Therefore, the objective of this work is to demonstrate that the use of ES helps to define urban parameters that aim to guarantee solar access to buildings, providing environmental comfort and habitability, as well as contributing to the reduction of energy consumption. Through a pilot study, three - dimensional computational simulations were carried out in Google SketchUp software, in unoccupied lots of two blocks of different zoning and with different urban parameters of this city, using the urban maximum indices of occupation. ES were generated in the Rhinoceros software with the aid of the DIVA and Grasshopper applications, with the minimum daily solar access interval to the buildings, defined based on the bibliographic review. Afterwards, the simulations (PDDIS and ES) were overlapped, which demonstrated that the current PDDIS does not guarantee solar access, requiring studies and instruments for its revision that ensure the right to the sun to its inhabitants.